Exploraciones morfológicas en texturas modulares (2016)
The results of a scan modeling are shown in addition to the study, review and discussion of architectural form. The basis for the expansion of an exploration into new morphological developments, such as the study of gradients and fragmentation processes scale in tissue formation and modular landscapes (and not just growth with relatively developed modules usually fixed sizes) are considered. They stand out as relevant and complementary notions of fragmentation and modular assembly based on units of different size and shape, in a minimalist framework of assimilation. Along with the above, cases are shown which were generated from exploring these principles applied to proposals developed by the author and students from commissions in the area of fractal geometry and Module Form Workshop City shown, related to the theme of vernacular architecture and urban fabric